Adaptatsiya sportsmenov k vypolneniyu spetsificheskikh statisticheskikh nagruzok - Belotserkovskii, Z. B.; Lyubina, B. G.; Kochina, N. G.; Podlivaev, B. A.; Bogdanova, E. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The general aim of this article was to analyze some physiological and methodological aspects of cardio-vascular system's reactions as a reply to static physical load. Among other goals, a quantitative evaluation of athletes' abilities to accomplish static loads, had become an important point of the research. It was stated the linnear dependence between physiological indicators of the motor activities and the volume of static load inside the limits of 15-20 kg. The above principle of testing can be used to indicate the capacities of wrestlers, weight-lifters, skaters, tourists, mountaineers.